(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The emergence of the internet of things spread across several sectors and the agricultural industry is not left out. The application of smart agriculture using IoT will improve productivity among stakeholders in the sector. It gives automation, control, and monitoring in agro-industry which leads to food sufficiency. This project was designed to address food sufficiency through smart agriculture using IoT. A methodic literature assessment (MLA) was adopted for this research where some research questions that we believe if addressed properly will increase food sufficiency were asked and answer with from literature. This project address the IoT sensor or devices and their application to achieve robust farming.